2015
DOI: 10.1159/000430338
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Regulatory B-Cells by Mesenchymal Stem Cells is Affected by SDF-1α-CXCR7

Abstract: Background/Aims: Mesenchymal stem cells (MSCs) possess immunomodulatory properties on a diverse array of immune cell lineages, including regulatory T and B cells (Tregs and Bregs, respectively). However, their specific effects and mechanisms underlying induction of Bregs remain unclear. The immune regulatory function of MSCs is exerted through both cell-cell contact and the release of soluble factors. The main objective of this study was to examine the role of the SDF-1-CXCR4/CXCR7 axis in the secretory action… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 41 publications
1
24
0
Order By: Relevance
“…These include, e.g., PGE2, TGFβ, IL2, IL6, hepatocyte growth factor (HGF), indoleamine 2,3-dioxygenase (IDO) [ 399 ], human leukocyte antigen (HLA), IL 1 receptor antagonist (IL1RA), CCL2, macrophage colony stimulating factor (M-CSF), and MSPC-secreted exosomes as paracrine mediators of MSPC immunosuppressive function ( Figure 4 ) [ 389 , 407 , 409 , 413 , 416 , 425 , 430 , 442 , 450 , 452 , 462 , 463 , 464 , 465 , 466 ]. The immunosuppressive cytokine IL10 is not produced by MSPCs themselves, but they induce other cell types to do this, in part via heme oxygenase-1 [ 443 , 460 , 467 ].…”
Section: Mspcs: Immunomodulationmentioning
confidence: 99%
“…These include, e.g., PGE2, TGFβ, IL2, IL6, hepatocyte growth factor (HGF), indoleamine 2,3-dioxygenase (IDO) [ 399 ], human leukocyte antigen (HLA), IL 1 receptor antagonist (IL1RA), CCL2, macrophage colony stimulating factor (M-CSF), and MSPC-secreted exosomes as paracrine mediators of MSPC immunosuppressive function ( Figure 4 ) [ 389 , 407 , 409 , 413 , 416 , 425 , 430 , 442 , 450 , 452 , 462 , 463 , 464 , 465 , 466 ]. The immunosuppressive cytokine IL10 is not produced by MSPCs themselves, but they induce other cell types to do this, in part via heme oxygenase-1 [ 443 , 460 , 467 ].…”
Section: Mspcs: Immunomodulationmentioning
confidence: 99%
“…Results from in vitro experiments show that while MSCs impair the proliferation and terminal differentiation of B cells (252) they have also been shown to stimulate antibody secretion (253). More recently, data have emerged which suggests that MSCs can promote the induction of regulatory B cells (Breg) (254). Neutrophils are an important mediator of the innate response and MSCs have been shown to enhance their survival through an IL-6-mediated mechanism, concomitant with the downregulation of reactive oxygen species, thereby conserving the pool of neutrophils primed to respond rapidly to infection (255).…”
Section: Clinical Application With Mesenchymal Stromal Cells For the mentioning
confidence: 99%
“…Recently, VEGF secretion by MSCs has been shown to have an important role in the survival of B cells through the activation of the AKT signaling pathway that inhibits the expression of caspase-3 [69]. MSCs directly promote the development of CD19 + CD24 high CD38 high IL-10-secreting regulatory B cells through the chemokine stromal derived factor-1 α (SDF-1 α ) and its receptor, CXCR7, which contribute to the generation of an immunosuppressive environment [70, 71]. Finally, in arthritis, we have shown that MSCs inhibit plasmoblasts generation in vivo in CIA through the expression of the IL-1 receptor antagonist (IL-1RA) on MSCs [18].…”
Section: Adaptive Immunity In Ra and The Effect Of Mscsmentioning
confidence: 99%